Oxygen Ion Escape at Venus Associated With Three‐Dimensional Kelvin‐Helmholtz Instability. Issue 6 (15th March 2022) - Dang, Tong; Lei, Jiuhou; Zhang, Binzheng; Zhang, Tielong; Yao, Zhonghua; Lyon, John; Ma, Xuanye; Xiao, Sudong; Yan, Maodong; Brambles, Oliver; Sorathia, Kareem; Merkin, Viacheslav
Abstract: How oxygens escape from Venus has long been a fundamental but controversial topic in the planetary research. Among various key mechanisms, the Kelvin‐Helmholtz instability (KHI) has been suggested to play an important role in the oxygen ion escape from Venus. Limited by either scarce in‐situ observations or simplified theoretical estimations, the mystery of oxygen ion escape process associated with KHI is still unsettled. Here we present the first three‐dimensional configuration of KHI at Venus with a global multifluid magnetohydrodynamics model, showing a significantly fine structure and evolution of the KHI. KHI mainly occurred at the low latitude boundary layer if defining the interplanetary magnetic field‐perpendicular plane as the equatorial plane, resulting in escaping oxygen ions through mixing with the solar wind at the Venusian boundary layer, with an escape rate around 4 × 10 24 s −1 . The results provide new insights into the basic physical process of atmospheric loss at other unmagnetized planet. Plain Language Summary: Kelvin‐Helmholtz instability (KHI) forms where there's a velocity difference across the interface between two fluids: For example, wind blowing over water. The KHI also commonly occurs when solar wind flows past a magnetized body. At Venus, the solar wind directly interacts with the Venusian ionosphere and KHI takes place at the induced magnetosphere. The KHI is often considered as an important source of ion escape and atmospheric loss of Venus, however, limited by either scarce satellite observations or simplified theoretical estimations, the mystery of the oxygen ion escape process associated with the KHI is still unsolved. In this letter, we present the first three‐dimensional (3D) KHI structures at the Venusian boundary layer, with a newly‐developed, global, high‐resolution, magnetohydrodynamic model. The KHI is well resolved and exhibits fine evolutions in the 3D global model. We have also found that the KHI could lead to significant escape of oxygen ions through mixing with the solar wind at the low latitude boundary layer of Venus. The KHI‐induced oxygen ion escape rate of 4 × 10 24 s −1 is comparable to the previous observation estimations. The results illustrate new insights into the atmospheric loss at the unmagnetized planets. Key Points: We present the first three‐dimensional (3D) Kelvin‐Helmholtz instability (KHI) structures at the Venusian magnetospheric boundary layer with a high‐resolution multifluid model The KHI is well resolved and exhibits dynamic and fine evolutions in the 3D global model KHI leads to significant escape of oxygen ions through mixing with the solar wind at the low latitude boundary layer of Venus